In vitro clonal propagation of locally cultivated pink colour Gladiolus var. Neelima through Cormel-sprout culture - S. U. Talukder, S. Subramaniam, M. H. Kabir, A. N. K. Mamun (Current Botany, 2016)
Micropropagation provides an economic advantage for the propagation of a particular crop like gladiolus, a beautiful flowering plant which emits expression of love. Propagation by conventional method is a slow process and pathogen keep on accumulation generation after generation which reduces yield and quality of flower and also generates insufficient propagules. An efficient propagation system could overcome those variabilities and meet the increasing demand of propagules production for the growing of gladiolus in the country while it is an exporting plant in Bangladesh. Moreover, establishment of a plant regeneration system through direct organogenesis or via callus is also a prerequisite to further in vitro genetic manipulation of the cultivar. Demand for disease free planting materials is increasing day by day and crop like vegetatively propagated plant is an appropriate means to generate propagules through in vitro techniques. Production of sufficient numbers of plants of a unique genotype is possible using in vitro culture system. In this study, the effect of various concentrations and combinations of plant growth regulators for in vitro regeneration of gladiolus was described using cormel-sprout as explants. However, an efficient in vitro plant regeneration protocol in locally cultivated pink colour Gladiolus var. Neelima was established on MS media with various hormonal supplements using cormel-sprout as explants. Ninety (90) percent of the explants responded for shooting on 0.5 mg/L BA + 0.5 mg/L Kin within the culture initiation period of 90 days. The average number of shoot per explants was 8 ±1.20 and the average shoot length of 12.40 ±2.15 cm were observed in this medium. Shoots are rooted well when they were excised individually and implanted on half strength of MS medium supplemented with 1.0 mg/l IBA, in which 90% of the shoot induced roots. The average number of root per shoot was 10 ± 1.20 and the average root length of 8.50 ± 1.25 cm were observed in this medium after culture of 30 days. Eighty (80) percent of the in vitro raised plantlets were survived in the natural environment.